Privacy’s Past: The Ancient Concept and Its Implications for the Current Law of Privacy - Keigo Komamura (Washington University Law Review, 2019)
Privacy is a mysterious concept. The more apparent its significance in the real world becomes, the more obscure the core and the limitations of the concept become. In the digital age, it is urgent that the legal framework to protect privacy should be enhanced more than ever before. At the same time, the right-based model of privacy which has long been dominant in theory and practice is now challenged by many privacy law experts who propose a shift from the right-based model to the trust-based model, a transition from the consent-based regime to the expectation-based regime, or from the user’s right to control to the fiduciary duties of professionals. This Article addresses the current debate and contributes to the ongoing search for a new concept of privacy by looking back at privacy’s past. As a legal formula, privacy was introduced at the end of the nineteenth century. However, we can trace its cultural origin to ancient Greek thought and the idea of a distinction between the public and the private realms that was inherent in the design and political structure of the polis. Relying on Hannah Arendt’s works, this Article draws some critical implications from the ancient idea and its modern turn, focusing on both the privative traits and the nonprivative traits of privacy. The argument is that the ancient Greek concept of privacy originally suggests a state of being deprived of relationships with others, and the implication is that privacy has been a relational concept since the beginnings of western political thought. This Article maintains that privacy law should seek its foundations in the nature of privacy as a component of the human condition, the existential fact that we all live with ambivalence between whether to disclose or conceal some aspect of our selves to others. This Article proposes that we shift away from thinking of privacy in relation to the demand to be “left alone” and think rather about the framing of regulative ideals for relation-building.
Keywords: Privacy; History of privacy; Privacy-as-trust; Privative traits; Nonprivative traits